City Identity Drawn from Intrinsic, Inherited and Imported Characteristics - Solesbury, William (Cambridge Scholars Publisher, 2021)
Cities commonly have well-known identities--New York as 'The Big Apple', Hong Kong as 'The Pearl of the Orient', and Beirut as 'The Paris of the East' are such examples. This book explores the nature of city identities, their composite characteristics, and how they have been shaped. It argues that they certainly draw on the influence of a city's present day circumstances: the goods and services it provides, how it is governed, its culture, its look and feel, and the customs of its people. However, an identity may also be shaped by a city's past, and its economic, social and physical inheritanc.